Elite Media Trends towards the Extent of Commitment of Kurdish Websites to the Ethics of the Profession in the Kurdistan Region : An Analytical Study - Azad Abdulazez Muhammad; Taher Hasso Zebari (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The present study’s aim is to investigate knowledge and determine media directions about the dependence of the Kurdish websites on professional ethics, performed in Kurdistan Region of Iraq. The samples were included in the present study are both websites from Rudaw and NRT, especially political and social news which were used as a study sampling. This study is a descriptive study in which analytical content methods were applied. The importance of the present study is that in the view scientific and academic views about all media departments of Colleges and Institutions. The scientific researchers who work on Professional ethics and modern media had been investigated poorly. On one hand, depending on the roles and influence of the electronic media about the level and the status of Kurdish media. One the other hand, the view and directions of the professional media staff along with these websites’ dependence on the professional ethics. Also, scientific attempt should be improved to determine the volume of the problem and seek the comparable solution of the same problem. The results of the scientific researches sometimes have positive impact on the media elements according to the practical and professional levels. If the results of the scientific research were taken in a valuable manner, the completed roles were achieved for journalism aspects of websites. The present study concluded that, the directions of the sampling method showed its independency toward the political and social cases along with some notes limited ratios of its dependency in some subjects and cases. More than half of the news samples of the study only showed one side expression, as in the majority of the news samples, the expressions were mixed with the news. Thus, these websites’ investigation is not as professional as needed.